2014
DOI: 10.1615/critrevimmunol.2014010267
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor-A (CD204): A Two-Edged Sword in Health and Disease

Abstract: Scavenger receptor A (SR-A), also known as the macrophage scavenger receptor and cluster of differentiation 204 (CD204), plays roles in lipid metabolism, atherogenesis, and a number of metabolic processes. However, recent evidence points to important roles for SR-A in inflammation, innate immunity, host defense, sepsis, and ischemic injury. Herein, we review the role of SR-A in inflammation, innate immunity, host defense, sepsis, cardiac and cerebral ischemic injury, Alzheimer’s disease, virus recognition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 155 publications
(237 reference statements)
3
116
0
7
Order By: Relevance
“…The class A macrophage scavenger receptor (SR-A) is a prototypic member of the scavenger receptor (SR) family, a collection of membrane receptors [20]. In recent years, several studies have revealed that SR-A has an essential influence on inflammation, ERS and cell apoptosis [21, 22]. Hydrogen sulfide (H 2 S), synthesized in the metabolic pathway that regulates the tissue concentration of sulfur-containing amino acids, is an endogenous gaseous mediator that exerts effects in the central nervous system and the cardiovascular system [23].…”
Section: Introductionmentioning
confidence: 99%
“…The class A macrophage scavenger receptor (SR-A) is a prototypic member of the scavenger receptor (SR) family, a collection of membrane receptors [20]. In recent years, several studies have revealed that SR-A has an essential influence on inflammation, ERS and cell apoptosis [21, 22]. Hydrogen sulfide (H 2 S), synthesized in the metabolic pathway that regulates the tissue concentration of sulfur-containing amino acids, is an endogenous gaseous mediator that exerts effects in the central nervous system and the cardiovascular system [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previously identified ligands included modified LDL variants, glycated albumin, glycated collagens, and b-amyloid fibrils. 30 Such modified proteins are undesirable in the circulation, which may explain why they are efficiently eliminated from the circulation by SR-AI. For FX, a rather distinct mechanism appears to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, computer modeling has suggested that the collagenous domain is responsible for mediating the uptake of negatively charged NMs [26] . Interestingly, SR-A receptors function by interacting with other membrane bound signaling and transport proteins to induce intracellular signaling pathways [27] . Signaling through SR-A can result in either pro-survival or pro-death pathways.…”
Section: Scavenger Receptor Class Amentioning
confidence: 99%
“…SR-A type receptors are primarily expressed on innate immune cells such as macrophages and dendritic cells where they facilitate endocytosis of ligands and cellular adhesion. SR-A type receptors are also expressed on the surface of fibroblasts, microglia, astrocytes, and endothelial, and epithelial cells [27] . Involvement of SR-A has been evaluated in a variety of diseases including atherosclerosis, sepsis, and bacterial and viral infections [27] .…”
Section: Scavenger Receptor Class Amentioning
confidence: 99%